Study of Novel Designs of Solar Air Heaters for Enhanced Thermo-hydraulic Performance - Kumar, Amit (IIT(BHU) Varanasi, 2021)
Abstract is available in the attachment.
UPLOADED BY IIT BHU
Keywords: Enhanced; nonlinear wave; Thermo-hydraulic; Solar Air Heaters